The memory laboratory : reclaiming and remebering the archeological fragments of Cape Town's original shoreline - Siebert, Erin (School of Architecture, Planning and Geomatics, 2017)
This thesis project began with an interest in public space and particularly the role of collective urban memory in reading and understanding public space in the city, as well as being a means of imbuing public space with meaning. This is closely linked to ideas of shared experience, identity and legacy. These ideas are widely discussed and debated in the making of architecture in our post colonial, post apartheid context. My interest is in the development of inclusive collective memories and how these histories become part of the everyday life of the city. Architecture and urban design play a key role in the spatial and physical expression of collective urban memory. This paper represents the body of work undertaken during this year long thesis investigation and provides the introduction to the architectural design project borne out of this research. The first part provides a theoretical basis for the project. Firstly it investigates the spatialization of memory in the human brain and relates this to the ways that collective memory has spatial implications in the urban environment. It also explores the development of a theory for collective memory. Secondly this section investigates the role of architecture in collective memory and reviews the typoolgies of memory architecture through examples of these typologies at work in Cape Town. It also reveals the development of memory architecture, in particular the 'museum ' through the ages. The second part of the paper is an exploration into the technology or making of buildings, and particularly looks at the role of time in the 'making' of architecture. This section is representative of my interest in the life story of buildings and investigates the way they change, adapt and are recycled or re-used over time. It considers the potential of flexibility (flex buildings) in creating sustainable architecture. This section also compiles the strategies, methodologies and lessons into a manifesto for sustainability through flexibility and therefore has been a useful design tool in the final parts of the thesis project. Part three is a study of urban memory in Cape Town, focussing particularly on the narratives and histories surrounding the original Cape shoreline. This particualr focus was chosen as it provides a platform for an inclusive history, comprising of multiple narratives and memories. It is representative of the natural history of Cape Town (landscape, climate, water) and the human history of indigenious inhabitants, early explorers, colonial immigrants, convicts and slaves. This section represents the compilation of archival research, literature searches, site exploration and mapping exercises, which provide the basis for the later design project. The fourth part of this paper represents the design component of the thesis. It elucidates the different parts of the design project and the research and analysis which provide the groundwork for the design. This section does not represent the final design, but rather illustrates the key design ideas, concepts and processes which will lead to the final design proposal.